An analysis report of a technology investment plan, specifically purchasing a chicken dressing machine, for the expansion and growth of REMIL poultry farm - Santos, Jeffrey Dela Rosa (University of the Philippines Diliman, 2013)
Poultry farming, broiler growing in particular, is one of the most common livestock in the Philippines alongside swine and cattle raising. This is actually due to an increase in the demand for chicken consumption throughout the country. Projected improvements in the Philippine economy as well as population growth are expected to continue to push-up consumption of chicken meat in the succeeding years. Moreover, the continued high retail price of pork may result in some shift from the latter to chicken by consumers. REMIL Poultry Farm (later on referred to as the "farm" in the succeeding paragraphs and sections) is a small-scale family business owned by Mr. Renato and Millie Santos from Baliuag, Bulacan. It is currently managed by Engr. Ana Meliza Santos, the owner's eldest daughter. For almost a decade, their business is typically growing chicks and selling them alive to haulers from Bulacan and Manila. Those haulers, commonly called as "viajeros", deliver the broilers to their customers in the wet markets. The farm usually conducts 5 to 6 harvest seasons in a year. Each season, the farm can support 10,000 chicks with a capital of around P1 million. Growing cycle starts on acquiring the chicks from the farm's trusted hatchery. Normally, the time required to raise the chicks until they are ready to be harvested is between 36 to 50 days (as soon as each chicken will have a live weight base of 1.5-1.9 kilograms). Regular feeding as well as scheduled medications is done manually. As for the latter, such task is to avoid contracting diseases and promote gains in weight. When ready to be harvested, the haulers collect the chickens and immediately deliver them to local markets. As per the manager, there are demands for wholesalers/retailers who prefer buying dressed chickens instead. This fact provided the idea of a technical expansion plan through acquiring a chicken dressing machine. This report is focused in formulating an analysis that would help REMIL Poultry Farm in deciding whether they are technically-and financially-ready in investing for the said machinery. Purchasing a technology (introduction of machinery) is one option of technology acquisition methods. This type is the quickest way and has the lowest risk of acquiring a technology. This is because of the proven acceptance of the said technology in the market. However, competitive advantage is limited considering that there is less to none introduction of new breakthroughs. The said option is also more of a market-driven strategy. This means that the approach used is always market-oriented and customer-oriented. Understanding what the customers do, understanding the customer's behaviours and measuring the interaction among customers are the factors leading to that concept. The haulers, in the farm's case, serve as their informant regarding the demands of the market. Ocular inspection is done to REMIL Poultry Farm in Baliuag, Bulacan. Interview with Engr. Santos is conducted to come up with the required information on the business' capability for a technical investment plan. Information gathering from related studies is given priority. Data showing the growth potential of dressed chicken for local consumption is proved and shown. Canvassing of local and foreign chicken dressing machine manufacturer is done to familiarize with each machine's features, technical specifications and prices. With the given factors above, locally branded machine are discovered to be more practical to buy than the foreign counterpart in terms of price. Moreover, it is easy to search and buy machine parts (such as rubber fingers) from the local manufacturer for maintenance purposes. Delivery coming from abroad would require bulk ordering as well as take some time and even cost more than purchasing locally. As for the comparison between using a chicken dressing machine and manual feather plucking, additional expenses are proved to be higher for the latter. Hiring of additional contractual workers is time consuming given the fact that the operation should be done, as much as possible, in less than a week in order for the dressed chickens to stay fresh. If not, the farm would need large cooling storage facility thus adding up to the capital expenses (CAPEX). There are poultry organizations that would readily share their knowledge with the technology investment similar to the introduction of machinery. Joining such group would enable a smooth knowledge sharing sessions among businessmen and supply chain companies. REMIL Poultry Farm is categorized as having an operative capability. The farm has the ability to implement, operationalize and repair an externally acquired technology, chicken dressing machine in this case, for the purpose of its technical expansion and growth. The analysis report is recommended as an integral guide for Engr. Santos' decision making process. The information related to the chicken dressing machine, especially the price, is subject to change as well as other factors thus making the credibility of the report limited in a short span of time. As soon as the manager verified and approved the report, it is highly recommended to start the plan on the 3rd Quarter of 2013. Aside from offering dressed chickens, another option would be engaging into contract breeding. However, this option is yet to be studied if applicable on REMIL Poultry Farm's current business setup. The integrator needs to assess the feasibility of the project first. Once approved, they will assist with the farm lay-out, poultry building design and construction, and other details that have direct impact on general flock health and management.